(3NRGfI Gdabgs - (3GdSeQbfOj, CHh GddjK, EeGe GdgOi, fUQ Hf eMeO Hf CMeO Hf EHQGgje, (B373 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg QH GdYGdejf bGd Gdabjg CHh GddjK GdSeQbfOj GYde Cf Gdabg Yde MSf hgh CLd ef SGjQ GdYdhe hbO GSJLeYJ aj gPG GdJCdja ef eSGFd Gdabg eYOhOI GdCLfGS hjSei NRGfI Gdabgs
(3BNQgG (B:s
(3aEPG Udi QcYI CNQi jJTgO GdSGHYI hcGf gh bO jfJgj ajeG jbVj aSLO ddSgh hJTgO GdKGefI Ke PcQ Cfg bQGAs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B8 / 27s
(3eYLe GdeDdajf (B4 / 24s
(3cTa GdXfhf (B1 / 703s
(3gOjI GdYGQajf (B2 / 490s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs